Intron retention as an excellent marker for diagnosing depression and for discovering new potential pathways for drug intervention - Okada, Norihiro; Oshima, Kenshiro; Maruko, Akiko; Sekine, Mariko; Ito, Naoki; Wakasugi, Akino; Mori, Eiko; Odaguchi, Hiroshi; Kobayashi, Yoshinori (Frontiers in Psychiatry, 2024)
BACKGROUND: Peripheral inflammation is often associated with depressive disorders, and immunological biomarkers of depression remain a focus of investigation.We performed RNA-seq analysis of RNA transcripts of human peripheral blood mononuclear cells from a case-control study including subjects with self-reported depression in the pre-symptomatic state of major depressive disorder and analyzed differentially expressed genes (DEGs) and the frequency of intron retention (IR) using rMATS.RESULTS: Among the statistically significant DEGs identified, 651 upregulated and 820 downregulated genes were enriched in the Gene Ontology term 'innate and adaptive immunity'. The upregulated DEGs were particularly enriched in the term 'bacterial infection and phagocytosis', whereas the downregulated DEGs were enriched in the terms 'antigen presentation' and 'T-cell proliferation and maturation'. We also analyzed 158 genes for which the IR was increased (IncIR) and 211 genes for which the IR was decreased (DecIR) in the depressed subjects. The Gene Ontology terms associated with IncIR and DecIR were very similar to those of the up-and downregulated genes, respectively, with a preponderance of the term 'ciliary assembly and function' for DecIR. Furthermore, the results of the network analysis also showed that a Japanese herbal medicine could partially alleviate the severity of depression in depressed patients. Including both IncIR and DecIR genes in the network analysis revealed several pathways related to the ability of patients to recover from depression.CONCLUSION: Depression was found to be associated with activation of the innate immune response and relative inactivation of T-cell signaling. The DEGs we identified reflect physiological demands that are controlled at the transcriptional level, whereas the IR results reflect a more direct mechanism for monitoring protein homeostasis. Accordingly, an alteration in IR, namely IncIR or DecIR, is a stress response, and intron-retained transcripts are sensors of the physiological state of the cytoplasm. In particular, the detection of altered IR in cilia-specific genes seems to correlate with defects in ciliary function or immunological synapse in depressed subjects. The results demonstrate the potential of relative IR as a biomarker for the immunological stratification of depressed patients and the utility of IR for the discovery of novel pathways involved in recovery from depression.